Loose Change Three women of the sixties - Davidson, Sara frey50 (Doubleday & Company, Inc. Garden City, NY, 1977)
This is a book about three women, and what happened to thme during a unique and turbulent decade in America, the 1960s.
Prologue - California girls (1943-63) - Blowing in the wind (1963-65) - Dawning of the age (1965-67) -Fighting in the street (1968-69) - Busy being free (1969-1971) - The day the music died (1971-73) - Winterlude (1973-?)
Keywords: Social conditions -- United States -- 1960-1980; Radicalism -- United States -- College students; Young women -- United States -- Biography